1998
DOI: 10.1021/jo980359u
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Some Oxygen-Containing Heterocycles by Radical Cyclization:  The Stereochemical Influence of Anomeric Effects

Abstract: The influence of the anomeric effect on radical cyclization has been examined by determining the stereochemical outcome of the ring closure of 10 suitably substituted radicals. The stereochemistry of the products formed from the acyclic precursors 4a-f indicates that for suitably constituted radicals anomeric interactions stabilize pseudoaxially substituted transition structures 14 thus affording products with stereochemistry the reverse of that normally observed.In recent times, the use of free radical reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Primary iodoalkene 1 d gave the 5‐ exo product 2 d (70 %; Table 1, entry 3). The O ‐homoallyl derivative 1 e gave the 6‐ exo product 2 e (Table 1, entry 4), which was obtained in relatively low yield, together with the directly reduced compound 2 e′ , thus showing, as expected, that the 6‐ exo ‐trig cyclization is less favored than the 5‐ exo ‐trig cyclization 14. The iodoalkyne 1 f gave 2 f through a 5‐ exo ‐dig cyclization (52 %; Table 1, entry 5).…”
Section: Methodssupporting
confidence: 54%
“…Primary iodoalkene 1 d gave the 5‐ exo product 2 d (70 %; Table 1, entry 3). The O ‐homoallyl derivative 1 e gave the 6‐ exo product 2 e (Table 1, entry 4), which was obtained in relatively low yield, together with the directly reduced compound 2 e′ , thus showing, as expected, that the 6‐ exo ‐trig cyclization is less favored than the 5‐ exo ‐trig cyclization 14. The iodoalkyne 1 f gave 2 f through a 5‐ exo ‐dig cyclization (52 %; Table 1, entry 5).…”
Section: Methodssupporting
confidence: 54%
“…The O-homoallyl derivative 1 e gave the 6-exo product 2 e ( Table 1, entry 4), which was obtained in relatively low yield, together with the directly reduced compound 2 e', thus showing, as expected, that the 6-exo-trig cyclization is less favored than the 5-exo-trig cyclization. [14] The iodoalkyne 1 f gave 2 f through a 5-exo-dig cyclization (52 %; Table 1, entry 5). The method was successfully extended to the reduction of tertiary iodide 1 g (94 %; Table 1, entry 6) and aryl iodides 1 h (96 %; Table 1, entry 7).…”
mentioning
confidence: 99%
“…Beckwith has reported that the acetal systems (Scheme 35, Equation b) behave quite differently from the non-acetal derivatives (Scheme 35, Equation a). 128 The stereochemical outcome of the non-acetal system (Equation a) was anticipated based on the well-established Beckwith-Schiesser-Houk 129-131 model for radical cyclization, where the main stereoisomer is produced through a chair-like transition state with all substituents in a pseudo-equatorial position (see Scheme 35). Interestingly, the acetal derivatives afford mainly the 2,5-cis disubstituted tetrahydrofurans in contravention to these guidelines.…”
Section: -Substituted 2-alkoxytetrahydrofuransmentioning
confidence: 99%